2019
DOI: 10.1002/dvdy.102
|View full text |Cite
|
Sign up to set email alerts
|

Activated Ras/JNK driven Dilp8 in imaginal discs adversely affects organismal homeostasis during early pupal stage in Drosophila, a new checkpoint for development

Abstract: Background Dilp8‐mediated inhibition of ecdysone synthesis and pupation in holometabolous insects maintains developmental homeostasis through stringent control of timing and strength of molting signals. We examined reasons for normal pupation but early pupal death observed in certain cases. Results Overexpression of activated Ras in developing eye/wing discs inhibited Ptth expression in brain via upregulated JNK signaling mediated Dilp8 secretion from imaginal discs, which inhibited ecdysone synthesis in proth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Pupal lethality has also been reported in D melanogaster strains harboring mutations in numerous other pathways, with a consensus that the arrests often appear to be caused by events that occurred earlier in development ( Shearn et al, 1971 ; Engels et al, 1987 ; Gildea et al, 2000 ; Yoshida et al, 2016 ; Kowalewski-Nimmerfall et al, 2014 ; Rosales-Vega et al, 2018 ; Syed et al, 2019 ; Drelon et al, 2019 ; Ray and Lakhotia, 2019 ; Wang et al, 2019 ; Yusuff et al, 2020 ). Having established that inositol is causing developmental defects, some next steps would be to determine if this is due inositol's role in membrane biogenesis, signal transduction, osmoregulation, as a carbon/energy source, as an insulin mimetic, or in some other component of maintenance of homeostasis and/or metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Pupal lethality has also been reported in D melanogaster strains harboring mutations in numerous other pathways, with a consensus that the arrests often appear to be caused by events that occurred earlier in development ( Shearn et al, 1971 ; Engels et al, 1987 ; Gildea et al, 2000 ; Yoshida et al, 2016 ; Kowalewski-Nimmerfall et al, 2014 ; Rosales-Vega et al, 2018 ; Syed et al, 2019 ; Drelon et al, 2019 ; Ray and Lakhotia, 2019 ; Wang et al, 2019 ; Yusuff et al, 2020 ). Having established that inositol is causing developmental defects, some next steps would be to determine if this is due inositol's role in membrane biogenesis, signal transduction, osmoregulation, as a carbon/energy source, as an insulin mimetic, or in some other component of maintenance of homeostasis and/or metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these studies show that when discs are damaged DILP8 signaling ensures that metamorphosis is delayed and growth of imaginal discs is slowed down, allowing regeneration of imaginal discs and symmetric growth of the adult organism. A role of dilp8 in interorgan signaling has also been shown in early pupae upon increased Ras/JNK signaling (18). However, adult roles of DILP8 signaling are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Ras V12 tumor-bearing larvae can initiate metamorphosis on time. However, most of them die before reaching adulthood, probably because of developmental defects [49]. Interestingly, Ras V12 clones trigger non-autonomous cell death in the surrounding wild type (wt) cells indicating that there is a sensing mechanism that mediates the detection of transformed Ras V12 cells by wt cells [50] (see the section on short-range interaction and cell competition).…”
Section: The Expression Of the Oncogene Ras V12 Alone Is Not Sufficient To Create Neoplastic Invasive Tumorsmentioning
confidence: 99%
“…Additionally, it has recently been shown that elevated Ras V12 in the eye discs leads to increased JNK signaling and further dilp8 upregulation in late larval stages. Although not able to prevent pupation alone, Ras V12 -mediated Dilp8 elevation lowers Ecdysone production so that after pupation, metamorphosis cannot proceed and the pupae die [49]. It is thus tempting to speculate that in Ras V12 ; scrib −/− eye disc tumors JNK signaling would be a major regulator of dilp8 expression and Ecdysone signaling impairment.…”
Section: The Tumor Halts the Larval Development And Gains More Time To Growmentioning
confidence: 99%